Implementation of Tahfizhul Qur’an Learning with Al-Qosimi Method - Sabiq, Ahmad Fikri; Ckamim, Abdul; Hidayah, Nur (Universitas Muhammadiyah Magelang, 2020)
The aim of this research is to find out the implementation of learning to Al-Qur'an cramming by using Al-Qosimi method along with the various obstacles that occur in it. The research is expected to become a reference and role model for learning to cramming the Qur'an, which is currently experiencing rapid development in various regions, both in formal and non-formal institutions. This research is a field research using a qualitative approach. Data collection techniques using interviews, documentation, and observation. The location of this research is in Al-Busyro School of Tahfizhul Qur'an Elementary (STTD), Sukoharjo. The interviewees were the principal, teacher and Ustadz Abu Hurri Al-Qosimi as the inventor of the Al-Qosimi method. The data analysis technique used data reduction flow, data presentation, and drawing conclusions. Meanwhile, the data validity checking technique uses triangulation. The results of this study indicate that Al-Qosimi method is a method of Qur'an cramming which is suitable to children. In the process, students are required to read memorized verses repeatedly. The Al-Qosimi method has three variants, MMUSBOB variant by reading repeatedly 25 times in 3 new rounds and then memorizing it, the MHL-PA variant by repeating 40 readings and then memorizing it, and the MMC variant which is a method of memorizing quickly by reading whole Qur'an at least 40 times. As a result, in 6 years students could memorize 18-20 juz for those not in the dormitory and 20-30 juz for those who were in the dormitory. The various variations of the Al-Qosimi method are almost the same, the only difference is the number of reading repetitions. This Al-Qosimi method is suitable to be applied to crammers of the Al-Qur'an from children to adults.